2012
DOI: 10.5539/jas.v4n8p60
|View full text |Cite
|
Sign up to set email alerts
|

Use of Factor Scores for Predicting Body Weight from Some Morphometric Measurements of Two Fish Species in Nigeria

Abstract: The interpretation of several traits contributing to body weight prediction is difficult due to the high degree of correlation among them. Based on this, we examined the relationships between body weight and six morphometric traits (standard length, total length, head length, body depth, dorsal length and caudal length) of two fish species, Oreochromis niloticus and Lates niloticus sampled in Doma Dam, Nasarawa State, Nigeria. The statistical approach adopted was the multivariate principal component factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…Besides that, Kokoszynski et al (2017) recorded shank length of different commercial broiler line was from 10.0 to 10.4 cm which is very close to the present findings. However, the studies by Yakubu et al (2009); Udeh and Ogbu (2011) observed that body length of commercial Arbor Acre broiler was 36.74 cm and Ross broiler was 37.12 cm at 8 weeks of age respectively, the values were slightly lower than the present study. This variation of morphometric parameters might be due to age, weight, and different types of commercial strain.…”
Section: Discussioncontrasting
confidence: 82%
“…Besides that, Kokoszynski et al (2017) recorded shank length of different commercial broiler line was from 10.0 to 10.4 cm which is very close to the present findings. However, the studies by Yakubu et al (2009); Udeh and Ogbu (2011) observed that body length of commercial Arbor Acre broiler was 36.74 cm and Ross broiler was 37.12 cm at 8 weeks of age respectively, the values were slightly lower than the present study. This variation of morphometric parameters might be due to age, weight, and different types of commercial strain.…”
Section: Discussioncontrasting
confidence: 82%
“…The results of the present study revealed that feathering rate traits measured at 7 and 10 days of age can be used successfully as predictors for BW at later ages in Japanese quail. Yakubu et al (2012) reported that multiple regression analysis could be used to deduce the complex relationships among BW and some morphometric measurements. Therefore, typically BW is regressed on morphometric measurements to determine a weight prediction equation.…”
Section: Discussionmentioning
confidence: 99%
“…Yakubu et al . (2012) reported that multiple regression analysis could be used to deduce the complex relationships among BW and some morphometric measurements. Therefore, typically BW is regressed on morphometric measurements to determine a weight prediction equation.…”
Section: Discussionmentioning
confidence: 99%
“…Momoh and Kershima (2008) developed both linear and multiple regression as predictors of BW in Nigerian local chickens, and found out that in both sexes the multiple regression equations when compared with the simple linear regression equations, multiple regression technique was better in predicting BW from linear body measurements than simple linear regression technique. Multiple regression analysis has been used to interpret the complex relationship among BW and some linear body measurements (Yakubu et al, 2012). Ukwu et al (2014) performed a statistical modeling of BW and linear body measurements in Nigerian indigenous chicken, the resultant predictive equations showed that there were significant relationships between BW and linear body measurements.…”
Section: Resultsmentioning
confidence: 99%